Age-related changes in functional connectivity between young adulthood and late adulthood1. Issue 10 (21st May 2015) - Xu, Xin; Kuang, Qifan; Zhang, Yongqing; Wang, Huijun; Wen, Zhining; Li, Menglong
<x xml:space="preserve">Abstract</x> The functional brain network in late adulthood has been found to show a significant difference from that in young adulthood using a variety of network metrics.